Analisis Pengaruh Tingkat Pemahaman Pajak Kos Terhadap Kepatuhan Wajib Pajak (Studi Kasus Pada Pemilik Usaha Kos di Kecamatan Umbulharjo Kota Yogyakarta) - Eliya Isfaatun; Dwi Priyanto (HOME, 2021)
ABSTRACT Tax revenue is important in increasing tax revenue in Yogyakarta. Tax rates for boarding houses with more than 10 (ten) rooms are set at 5% (five percent). Increase tax revenue which is supported by an understanding of the tax owned by the boarding house owner, so that he complies with taxation. This research is intended to study the level of understanding of taxes for taxpayer assistance. This type of research is quantitative research. The population in this study is the owner of a tax business in Yogyakarta's Umbulharjo District which holds 710 people. The sampling technique used is the Slovin technique, which is a boarding business owner in the Umbulharjo District of Yogyakarta City which holds 256 people. The instrument used was a questionnaire. Data analysis techniques using the validity and reliability test, normality test, linearity test, simple regression analysis, t test, and the coefficient of determination test. The results showed there were significant and significant differences in the level of tax understanding of tax liabilities. This is evidenced through the t test with the results of t count 15.920> t table 1.650 and the regression equation Y = 14.516 + 0.671X. From these results it means that the higher the cost of income tax, the higher the taxpayer approval. This is also supported by a significance value of 0,000, which means this significance value is less than 0.05. Key Words: understanding boarding tax, tax obligations, boarding businesses in Umbulharjo District